Guidelines for Dealing with Labor Shortages at the Operational Level in the Industrial Sector for Sustainability - Wattanavit Tadtiam; Dr. Thitirat Thawornsujaritkul; Dr. Thanin Silpcharu (Migration Letters, 2023)
Operational-level workers play a crucial role in running a business and generating income. When the industrial business sector has an adequate labor force, it leads to continuous business growth, thereby influencing economic expansion in the sector. This research aims to explore strategies for addressing the labor shortage at the operational level in the industrial business sector to ensure sustainability. It is developed into a structural equation model. The research encompasses both qualitative and quantitative methods. It involves surveying quantitative data from questionnaires distributed to 500 human resources executives from industrial business organizations. By employing descriptive statistics, inferential statistics, and multivariate statistics. The research findings provide guidance on managing labor shortages at the operational level in the industrial business sector with a focus on sustainability. The four elements are ranked in order of importance as follows: 1) Corporate image (X ̅ = 4.47), 2) Compensation and benefits (X ̅ = 4.45), 3) Organizational culture (X ̅ = 4.44), and 4) Workforce analysis and planning (X ̅ = 4.43). Regarding the hypothesis testing results, it was found that there is no significant difference in dealing with the labor shortage situation at the operational level in the industrial business sector for sustainability between small and medium-sized business organizations and large business organizations at the 0.05 significance level. Moreover, the analysis of the developed structural equation model demonstrated that it meets the evaluation criteria and aligns with the empirical data. The chi-square probability level was 0.140, the relative chi-square value was 1.120, the consistency index value was 0.966, and the root mean square index of error estimation was 0.015.